(untitled) (The Pakistan Development Review, 2004)
This paper attempts to analyse the impact of trade liberalisation on the skilledunskilled wage gap and the level of welfare of developing countries, which are generally characterised by large “informal” labour markets. A neo-classical full-employment foursector model has been developed, where the informal sector produces either a final product or an intermediate product on subcontracting basis. Evidence shows that in either case, trade liberalisation, in the form of an increase in foreign capital inflow, widens the skilled-unskilled wage gap of the economy under some reasonable conditions. It also shows that as a result of an increase in the foreign capital inflow, the level of welfare of the economy increases, when the informal sector produces a final product. However, when the informal sector produces an intermediate product on subcontracting basis, the level of welfare of the economy falls.